Draft Annual Plan 1987-88 Vol. I (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1987)
Under Plant protection programmes it is proposed to Provide 25% subsidy on wheat weedicides. The aerial spray for mustard crop in Gurgaon and Mohindergarh districts would be arranged free of cost Aerial spray on cotton is arranged at subsidised rates i. e. Rs 40/-are charged per acre per spray from cultivators against actual cost of Rs 92/-per acre per spray.
Planning Department, Government of Haryana